EVALUATING HOSPITAL READINESS FOR HEALTH EMERGENCIES: A CASE STUDY OF COVID-19 READINESS IN INDONESIA - Jarghon, Ali E M; Damayanti, Nyoman Anita; Dhamanti, Inge (International Journal of Patient Safety and Quality, 2024)
Background: It is important to evaluates the readiness of hospitals in response to health emergencies, focusing on their ability to manage crises effectively. The objective of this study was to assess the hospitals' readiness across multiple key components as defined by the WHO hospital readiness checklist. Method: A cross-sectional study design was used to assess the readiness of 59 hospitals over 2021 and 2022. Data were collected through the WHO checklist, evaluating 12 components such as leadership, communication, surveillance, and resource management. The hospitals were evaluated quarterly to track changes in readiness levels over time. Descriptive statistics were used to analyze the overall readiness scores for each hospital. Results: Leadership, incident management, and infection prevention and control remained consistently strong during the study period. However, notable weaknesses were found in occupational health, mental health support, and the continuity of essential services, which scored the lowest. Although there were minor improvements in maintaining essential services in 2022, these areas still need considerable improvement. Conclusions: The study concludes that, despite strong leadership and infection control measures, hospitals in the region need targeted interventions to address gaps in mental health support and service continuity. Improving these areas is critical for achieving comprehensive disaster readiness and enhancing hospital resilience to future health crises and natural disasters.